2014
DOI: 10.4018/978-1-4666-4373-4.ch012
|View full text |Cite
|
Sign up to set email alerts
|

How to Value and Monitor the Relational Capital of Knowledge-Intensive Organizations

Abstract: Knowledge management systems are a way to help tracking and keeping organizational knowledge. Typically, organizations value is greater than their tangible assets value. Human, structural, and relational capital is essential knowledge but difficult to evaluate because it tends to be tacit and spread in different organizational elements. The relational capital, as tacit knowledge, is not possible to capture its value as from accounting systems. There is a lack of models to evaluate the relational capital of org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…As depicted in Fig. 3, we found that predominant relational capital value refers to the Information Share relational action, and relational action Problem has the lowest RCV [15]. …”
Section: A Case Study: Vodafonementioning
confidence: 95%
See 4 more Smart Citations
“…As depicted in Fig. 3, we found that predominant relational capital value refers to the Information Share relational action, and relational action Problem has the lowest RCV [15]. …”
Section: A Case Study: Vodafonementioning
confidence: 95%
“…Vodafone case study was focused on the analysis of the relational capital of six teams from a Vodafone Portugal Unit: GSS [15].…”
Section: A Case Study: Vodafonementioning
confidence: 99%
See 3 more Smart Citations